How RPG (Role Play Games) Impact Players’ English Ability - Khair, Miftahul (La Parole : Journal of Language Teaching and Pedagogy, 2022)
In today's digital era, playing games is no stranger to people all over the world. Especially for young subjects. RPG (Role Play Game) is one of the most played games by gamers from all over the world. Because having a good story is one of the most important things in this game. The reason is, the players have to interact with the NPC (Non Player Character). English is the only language they interact with. Plus the players always play with players from other countries. Considering that the players interact a lot using English, it makes them unknowingly learn language skills and language components. This study aims to describe and interpret the players' experience in playing RPG and its relation to learning language skills and language components that they learn while playing, as well as revealing how English skills can influence the emotions of the players. Phenomenological research is the type of research used. This type of research is in accordance with the topic used, because it helps researchers in finding the essence or meaning of RPG and its relationship with the players' English learning. There were three participants involved in this study. The three participants are players who have a lot of experience in playing RPG games, and have high playing skills so that researchers get detailed answers and explanations about their experiences in playing. The results of this study indicate that there are many interactions in English carried out by the players. Like listening to and reading instructions, expressing ideas and feelings by speaking or writing them, the players accidentally learn English. In addition, the player's English skills.